71 A MOBILITY PROFILE OF THE PATIENTS ADMITTED TO AN ESD SERVICE IN IRELAND. (25th October 2022) - Crowley, A; Dhochartaigh, DN; Murphy, A; Gough, D; Fitzpatrick, M
Abstract: Background: Early Supported Discharge (ESD) allows patients to receive multidisciplinary stroke rehabilitation in their own home upon discharge from the acute hospital setting. ESD is recognised as international best practice for patients with mild to moderate impairments post stroke. An ESD team was set up in September 2020 from an acute hospital. A retrospective audit was carried out to profile the mobility of patients referred to the physiotherapy ESD service. Methods: A retrospective chart audit was carried out on 42 patients referred to physiotherapy during the first six months of the ESD service. Data was collected on admission and discharge from hospital, for those patients being referred to ESD on the following: age, mobility, Berg Balance Scale score and length of stay. Results: The mean age of the patient group was 70 (range 41 – 80 years). On discharge to ESD, 80 % of patients were independently mobile with or without an aid . Supervision or assistance of one person was required by 20% of patients. Thirty percent of patients were off their baseline mobility on discharge to the ESD service. The average Berg Balance Scale score was 51. The mean length of inpatient stay for ESD patients was 12 days compared to 33 days for those awaiting offsite rehabilitation. Conclusion: This data demonstrates that the majority of patients admitted to ESD were independent with mobility. This patient cohort most likely required higher level physiotherapy interventions such as exercise tolerance progression, community integration and upper limb rehabilitation. Further research should evaluate the range of interventions provided within this ESD physiotherapy service.